Current approaches to evaluate the function of cytotoxic T-cells in non-human primates. Issue 1 (31st December 2023) - Kamperschroer, Cris; Frank, Brendon; Genell, Caroline; Lebrec, Hervé; Mitchell-Ryan, Shermaine; Molinier, Brigitte; Newsome, Courtni; Piche, Marie-Soleil; Weinstock, Daniel; Collinge, Mark; Freebern, Wendy; Rubio, Daniel
Abstract: Cytotoxic T-lymphocytes (CTL) are a subset of T-cells that play a critical role in protecting against intracellular infections and cancer, and have the ability to identify and kill infected or transformed cells expressing non-self peptides associated with major histocompatibility (MHC) Class I molecules. Conversely, aberrant CTL activity can contribute to immune-related pathology under conditions of overwhelming infection or autoimmunity. Disease-modifying therapeutics can have unintended effects on CTL, and a growing number of therapeutics are intended to either suppress or enhance CTL or their functions. The susceptibility of CTL to unintended effects from common therapeutic modalities underscores the need for a better understanding of the impact that such therapies have on CTL function and the associated safety implications. While there are reliable ways of quantifying CTL, notably via flow cytometric analysis of specific CTL markers, it has been a greater challenge to implement fit-for-purpose methods measuring CTL function in the context of safety studies of therapeutics. This review focuses on methods for measuring CTL responses in the context of drug safety and pharmacology testing, with the goals of informing the reader about current approaches, evaluating their pros and cons, and providing perspectives on the utility of these approaches for safety evaluation.